Plastic decomposition method

JP2025021482APending Publication Date: 2025-02-14WASEDA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023124728
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0019】 本発明に係るプラスチックの分解方法によれば、廃プラスチックを含むプラスチックを、ゼオライト触媒と溶媒として軽油を用いて混合、加熱して反応させてプラスチックを分解するようにしている。よって、ゼオライト触媒がプラスチックの分解を促進するとともに、溶媒として軽油を使用することで、分解対象のプラスチックの流動性が上がり、プラスチックを加熱して融かした際に高粘度となるという問題を解消でき、その結果、廃プラスチックを含むプラスチックを速やかに均一に加熱し、高い分解率で分解でき分解能が高いとともに、石油化学原料として使用できるC3~C9成分を高収率で得ることができる。本発明に係るプラスチックの分解方法は、分解対象を廃プラスチックとした、廃プラスチックを分解する方法として最適である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021482000001_ABST
    Figure 2025021482000001_ABST
Patent Text Reader

Abstract

To provide a plastic decomposition method capable of decomposing plastic including waste plastic with a high decomposition rate and high resolution, and obtaining components usable as petrochemical feedstock at a high yield.SOLUTION: The plastic decomposition method according to the present invention comprises mixing plastic including waste plastic with a zeolite catalyst and light oil as a solvent, heating and reacting the mixture to decompose the plastic. Thus, the zeolite catalyst promotes the decomposition of the plastic, and the use of the light oil as a solvent increases the fluidity of the plastic to be decomposed, solving the problem of high viscosity when the plastic is heated and melted. As a result, the plastic can be heated quickly and uniformly, decomposed with a high decomposition rate and high resolution, and C3 to C9 components usable as petrochemical feedstock can be obtained at a high yield. The present invention is optimal as a method for decomposing waste plastic, with the decomposition target being waste plastic.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for decomposing plastics, and more particularly to a method for decomposing plastics, including waste plastics, with a high decomposition rate, capable of obtaining C3 to C9 components that can be used as petrochemical raw materials in high yields. [Background technology]

[0002] The disposal of large amounts of waste plastic has become a social issue. For example, in Japan, approximately 8.2 million tons of waste plastic is discharged, but only approximately 21% and 4% are recycled through material recycling and chemical recycling, respectively, while approximately 62% is recovered as energy, and the remaining approximately 13% is simply incinerated or landfilled.

[0003] Here, material recycling (MR) is a method of physically breaking down waste plastic into small pieces and using them as raw materials for products. Chemical recycling (CR) is a method of chemically breaking down waste plastic and using them as raw materials for products. Furthermore, energy recovery (ER) is a method of recovering and using the thermal energy generated when incinerating waste plastic, and is also called thermal recycling in Japan.

[0004] As mentioned above, energy recovery accounts for the majority of waste plastic recycling methods, but there are problems with energy recovery, such as the fact that plastic cannot be used as a resource, and that what is called thermal recycling in Japan is not considered recycling in Europe and the United States. In addition, the Basel Convention restricts the export of waste plastic, and there is also the restriction that waste plastic must be treated within the country where it is generated.

[0005] In view of the above, and in order to reduce greenhouse gas emissions and promote carbon circulation, technological development of material recycling and chemical recycling is being actively promoted. These methods are desirable from the viewpoint of reducing the environmental load, as they can convert waste plastics into raw materials for products and reuse them, and thus curb the consumption of limited natural resources and reduce the amount of landfill disposal through the cyclical use of resources. Against this background, various means for decomposing plastics have been proposed (see, for example, Patent Documents 1 to 3, etc.).

[0006] In the field of chemical recycling, waste plastics have been used so far as incineration ash in cement manufacturing, as a blast furnace reducing agent, and as a chemical raw material in coke ovens. However, these technologies have been problematic in terms of resource circulation, since waste plastics ultimately become carbon dioxide. In recent years, the importance of chemical recycling technologies such as conversion to oil, gasification, and raw material monomerization without combustion, which produce substances closer to plastic materials, has been increasing as a measure for making more effective use of waste plastic materials (see, for example, Patent Document 4, etc.). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2018-520247 [Patent Document 2] Special Publication No. 2018-524448 [Patent Document 3] Patent No. 6130358 [Patent Document 4] Patent No. 7258270 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0008] Chemical recycling is important in a sustainable society aiming for zero carbon, especially because of the expectation that petrochemical raw materials (e.g., C3 to C9 components, etc.) can be produced from relatively low-quality waste plastics, and technological development is being promoted worldwide. However, there are problems with waste plastics, such as their low thermal conductivity and high viscosity when melted by applying heat, the low decomposition rate (conversion rate) of plastics by thermal decomposition alone, and the difficulty of increasing the yield of petrochemical raw materials.

[0009] The present invention has been made in consideration of the above, and aims to provide a plastic decomposition method that can decompose plastics, including waste plastics, at a high decomposition rate, has a high decomposition ability, and is capable of obtaining C3 to C9 components that can be used as petrochemical raw materials in high yields. [Means for solving the problem]

[0010] In order to solve the above problems, the method for decomposing plastics according to the present invention comprises the steps of: The method is characterized by using debased and / or hydrotreated diesel as a solvent, mixing plastics (including waste plastics) with a zeolite catalyst, and heating to cause a reaction.

[0011] The plastic decomposition method according to the present invention is characterized in that, in the above-described present invention, the zeolite catalyst has a 10-membered ring or a 12-membered ring.

[0012] The plastic decomposition method according to the present invention is characterized in that, in the present invention described above, the zeolite catalyst is a 12-membered ring Beta zeolite catalyst.

[0013] The plastic decomposition method according to the present invention is characterized in that, in the present invention described above, the light oil is LGO (Light Gas Oil).

[0014] The plastic decomposition method according to the present invention is characterized in that, in the above-described present invention, the zeolite catalyst has been treated with an alkali.

[0015] The plastic decomposition method according to the present invention is characterized in that, in the present invention described above, the heating temperature is 350 to 450°C.

[0016] The method for decomposing plastics according to the present invention is characterized in that, in the present invention described above, the plastics are waste plastics.

[0017] The method for decomposing plastics according to the present invention is characterized in that in the present invention described above, the decomposition rate of the plastics is 80% or more.

[0018] The plastic decomposition method according to the present invention is characterized in that in the above-described present invention, the yield of C3 to C9 components is 50% or more. Effect of the Invention

[0019] According to the plastic decomposition method of the present invention, plastics including waste plastics are mixed with a zeolite catalyst and diesel as a solvent, and are heated to react and decompose the plastics. Thus, the zeolite catalyst promotes the decomposition of the plastics, and the use of diesel as a solvent increases the fluidity of the plastics to be decomposed, which solves the problem of high viscosity when the plastics are heated and melted. As a result, the plastics including waste plastics can be heated quickly and uniformly, decomposed at a high decomposition rate, and the decomposition ability is high, and C3 to C9 components that can be used as petrochemical raw materials can be obtained in high yields. The plastic decomposition method of the present invention is optimal as a method for decomposing waste plastics, in which the decomposition target is waste plastics. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a graph showing the relationship between external surface area and decomposition rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] One aspect of the present invention will be described below.

[0022] The method for decomposing plastics according to the present invention comprises the steps of: Using debased and / or hydrotreated diesel as a solvent, adding plastics (including waste plastics) and a zeolite catalyst to the solvent, mixing them, and heating them to cause a reaction; Includes the following as basic components.

[0023] In the plastic decomposition method according to the present invention (hereinafter sometimes simply referred to as the "decomposition method according to the present invention" or "decomposition method"), the plastics to be decomposed are polyolefin-based plastics, such as polyethylene and polypropylene, including polyvinyl chloride, and are basically a concept excluding thermosetting resins such as epoxy resins (note that when the decomposition target is waste plastic or contains waste plastic, unintended thermosetting resins may be mixed in, in which case they will have to be included), and the concept of the plastics to be decomposed also includes waste plastics. Furthermore, the shape of the plastics is arbitrary, and it does not matter whether they are in the form of raw materials (pellets) or in the form of molded bodies.

[0024] Plastics can be either a single type or a combination of two or more types. When waste plastics are to be decomposed, they may consist of one type, but in most cases they are thought to consist of two or more types.

[0025] Examples of target plastics include polypropylene (PP), polyethylene (PE), propylene ethylene copolymer, polystyrene (PS), polybutene, ethylene oligomer, butene oligomer, styrene oligomer, polyethylene terephthalate, polybutylene terephthalate (PET), polycarbonate, nylon, etc. Among these, examples of polyethylene include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, etc.

[0026] Examples of chlorine-containing plastics include polyvinyl chloride (PVC), polyvinylidene chloride, etc. As described above, the plastics covered include waste plastics, and may be one of the above-listed plastics or a mixture of two or more of these plastics.

[0027] The plastics including waste plastics preferably contain at least one plastic derived from polyolefins (e.g., polyethylene, polypropylene, propylene ethylene copolymer, polystyrene, polybutene, ethylene oligomer, butene oligomer, styrene oligomer, etc.).

[0028] In addition, the plastics to be decomposed include waste plastics (waste plastics), but generally, waste plastics often contain the 3Ps mentioned above (polypropylene (PP), polyethylene (PE), and polystyrene (PS)), and may also contain other plastic materials such as polyvinyl chloride (PVC) and polyethylene terephthalate (PET).

[0029] The catalyst used is a zeolite catalyst, which is a solid acid catalyst. Zeolite catalysts are inexpensive and widely used industrially, and have the advantages of having strong acid sites and shape selectivity. Plastics such as polypropylene swell and melt in the solvent, and during the reaction, they penetrate into the outer surface and pores of the zeolite catalyst and decompose (note that if the plastic molecules are not linear but close to spherical, they may not be able to penetrate the pores because their cross-sectional area is too large compared to the pores of the zeolite catalyst). The molecular chains become shorter, and the cut molecular chains enter the pores of the zeolite catalyst, and it is thought that C3 to C9 components that can be used as petrochemical raw materials are produced in high yields in the pores, which have strong acid sites and have an overwhelmingly larger surface area as a reaction field than the outer surface.

[0030] The zeolite catalyst is not particularly limited, but it is preferable to use a 10-membered or 12-membered ring zeolite catalyst. Specifically, for example, ZSM-5, ferrierite, etc. can be used as the 10-membered ring, and for example, Beta type, USY (Ultrastable Y), EMT, Y type, mordenite, MTW, etc. can be used as the 12-membered ring, and for example, CIT-1, etc. can be used as the 10-membered and 12-membered ring. These zeolite catalysts may be used alone or in combination of two or more.

[0031] It is particularly preferable to use a 12-membered ring beta type zeolite catalyst (beta zeolite catalyst). The beta zeolite catalyst may be a commercially available synthetic zeolite or a zeolite catalyst obtained by a fluoride method.

[0032] The fluoride method is a method of synthesizing a zeolite catalyst by using a fluoride such as ammonium fluoride (NH4F) or sodium fluoride (NaF) with fumed silica (SiO2). For example, the fluoride method can be easily carried out by mixing fumed silica (SiO2), tetraethylammonium hydroxide (TEAOH), ammonium fluoride (NH4F), aluminum hydroxide (Al(OH)3), etc., stirring, aging, etc., and then subjecting the mixture to hydrothermal synthesis, and filtering, drying, calcining, etc., of the product.

[0033] In addition, examples of commercially available synthetic zeolites that can be used include high silica zeolite HSZ (registered trademark) (HSZ-900 931HOA (Si / Al=15.1) (manufactured by Tosoh Corporation)) and CP814E (Si / Al=12.5) (manufactured by ZEOLYST).

[0034] Regarding the Si / Al ratio (silica / alumina ratio) of the zeolite catalyst, the number of active sites increases as the Si / Al ratio approaches 1. In the present invention, however, it is generally preferable that Si / Al=1 to 100, and particularly preferable that it is 2 to 40.

[0035] The shape of the zeolite catalyst is not particularly limited, and various shapes such as granular (particulate), powdery, and spherical can be used. The particle size (average particle size) of the zeolite catalyst is also not particularly limited, but is preferably 0.1 to 50 μm, and particularly preferably 0.1 to 10 μm, but is not particularly limited to this range. The zeolite catalyst may be classified to make the (average) particle size uniform. When the zeolite catalyst is used industrially, it is used after adding a binder such as alumina, firing, and molding (for example, 0.5 μm particulate zeolite catalyst is molded into a sphere to make it 70 μm). In this case, the particle size of the catalyst particles may be several tens of μm to several cm. The particle size may be specified by confirming with a microscope, etc., and the average value of an appropriate number may be used as the average particle size.

[0036] The zeolite catalyst is preferably subjected to an alkali treatment, which increases the external surface area of ​​the zeolite catalyst, thereby enabling the decomposition of plastics to be carried out efficiently.

[0037] The method of alkali treatment of the zeolite catalyst is not particularly limited, and any conventionally known alkali treatment method can be used. That is, the alkali treatment can be simply performed by immersing the zeolite catalyst in an alkaline aqueous solution, which is a basic solution.

[0038] The alkaline aqueous solution can be easily carried out by immersing the zeolite catalyst in an alkaline aqueous solution such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonia (NH3) water, organic amine, etc., and stirring the solution while heating it to a temperature of, for example, 20 to 800° C. The molar concentration of the alkaline aqueous solution is not particularly limited, but is preferably, for example, 0.01M to 1M.

[0039] Furthermore, since the zeolite catalyst thus treated with an alkali becomes an alkali salt (when an aqueous solution of sodium hydroxide is used as the aqueous solution, it becomes a sodium salt), it is preferable to carry out an ion exchange treatment after filtering and drying.

[0040] When the ion exchange treatment is performed using the above-mentioned aqueous sodium hydroxide solution as the alkali treatment, for example, an aqueous solution of ammonium nitrate (NH4NO3), hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), etc. can be used, and the alkali-treated zeolite catalyst is immersed in the solution and stirred while being heated to a temperature of 20 to 90° C. The molar concentration of the aqueous solution for carrying out the ion exchange treatment is not particularly limited, but is preferably, for example, 0.1 M to 5 M.

[0041] The zeolite catalyst that has been subjected to the alkali treatment and the ion exchange treatment is dried and then calcined, for example, at a temperature of 400 to 700° C., though there is no particular limitation. The time for calcination is preferably 2 to 20 hours, though there is no particular limitation.

[0042] The zeolite catalyst to be treated with alkali is preferably one having a high degree of crystallinity (good crystallinity). In this regard, the zeolite catalyst obtained using the above-mentioned fluoride method has a relatively high degree of crystallinity, and is therefore preferable as a target for the alkali treatment (synthetic products and the above-mentioned commercially available products often have their structure destroyed when subjected to alkali treatment).

[0043] On the other hand, when the activity of a beta zeolite catalyst is improved by performing an alkali treatment using an alkaline aqueous solution such as an aqueous sodium hydroxide solution, the structure may be destroyed if the original zeolite does not have a high degree of crystallinity (good crystallinity). Therefore, it is preferable to use a zeolite catalyst obtained by the fluoride method, which synthesizes a beta zeolite catalyst with a high degree of crystallinity, as the zeolite catalyst to be subjected to the alkali treatment.

[0044] In addition, the external surface area of ​​the zeolite catalyst increases by alkali treatment, and the decomposition rate (also called the conversion rate; the same applies below) of the plastics and solvents to be decomposed tends to increase in accordance with the size of the external surface area, including that of the alkali-treated zeolite catalyst.

[0045] As a solvent for decomposing plastics, light oil (light oil fraction) containing a large amount of paraffinic hydrocarbon compounds (hereinafter, sometimes simply referred to as "paraffin" or "paraffin fraction"), such as LGO (Light Gas Oil), LCO (Light Cycle Oil), and VGO (Vacuum Gas Oil), which are petroleum fractions supplied from petroleum refineries, can be used. These light oils as solvents can be used alone or in combination of two or more types. By using these solvents, the fluidity of the plastic to be decomposed increases, which solves the problem of high viscosity when the plastic is heated and melted.

[0046] In the present invention, the solvent used is assumed to be a hydrocarbon solvent obtained by petroleum refining, and various light oil fractions such as the above-mentioned LGO (light gas oil), LCO (light cracked gas oil), and VGO (vacuum gas oil) are adopted.

[0047] As for the solvent, the plastic decomposition oil obtained by the decomposition method of the present invention ((3) in the decomposed components below) can be reused as the solvent. These are assumed to be hydrocarbon solvents with a similar composition to the above-mentioned light oil (light oil fraction), such as LGO and VGO (because it is assumed that components with a carbon number of 20 or more among the plastic decomposition products have such a composition).

[0048] It is preferable that the solvent made of diesel contains a large amount of paraffin (paraffin content, saturated content) which has a relatively high boiling point (e.g., 280°C or higher) compared to the whole. For example, 10 ~C 30It is preferable that the solvent contains linear paraffins and branched paraffins. The solvent used, including these paraffins, is not particularly limited, but it is preferable that the solvent contains 50% or more of paraffin (paraffin content) relative to the total, and it is particularly preferable that the solvent contains 70% or more of paraffin. In consideration of the fact that the solvent contains a large amount of paraffin, it is preferable to use LGO as the solvent. LGO is generally a fraction distilled at about 240 to 360°C from crude oil, and contains 70% paraffin, 25 to 30% aromatics (of which the aromatic content of 3 or more rings is a few percent, and most are 2-ring aromatics), about 1% sulfur, and 0.01 to 0.02% nitrogen. The sulfur content is benzothiophene / dibenzothiophene, and the nitrogen content is 2 / 3 of 5-membered ring N and 1 / 3 of 6-membered ring N.

[0049] In the present invention, these diesel fuels need to be subjected to debasing treatment and hydrogenation treatment (hydrodesulfurization treatment). By removing (desorbing) the base from the solvent by debasing treatment, and by decomposing and removing compounds containing impurities such as sulfur, nitrogen, oxygen, and metals from the solvent by hydrogenation treatment, the decrease in catalyst activity is suppressed, and as a result, the decomposition rate of plastics is improved. The solvent may be subjected to either the debasing treatment or the hydrogenation treatment, or both.

[0050] The debasing treatment can be easily carried out by adding a solid acid such as amorphous silica alumina to a target solvent such as LGO at a ratio of 1 to 20 mass % and stirring for 0.5 to 10 hours to adsorb the basic substance to the solid acid.

[0051] Hydrotreating, also known as hydrodesulfurization, is a process in which impurities (e.g., sulfur, nitrogen, oxygen, metals, etc.) are decomposed and removed by contacting petroleum fractions with a catalyst containing nickel, molybdenum, or cobalt, etc., together with hydrogen, under a specified high temperature and pressure. LGO usually contains about 0.5 to 6 mass% sulfur, so hydrodesulfurization is used to ensure that such impurities, such as sulfur components, are removed. Hydrotreated LGO (desulfurized LGO) is LGO that has been hydrodesulfurized to reduce the sulfur content to 10 ppm or less. During this process, most of the nitrogen disappears, the aromatics are hydrogenated to 20% or less, and naphthenes also increase.

[0052] In the decomposition method according to the present invention, the plastic and the zeolite catalyst are mixed in the solvent and heated to cause a reaction. The temperature during the heating (heating temperature) can be appropriately adjusted depending on the type and amount of the plastic to be decomposed, the type and amount of the solid acid catalyst and the hydrocarbon solvent used, and the heating time (described later), but is preferably about 300°C or higher, more preferably 330 to 500°C, and particularly preferably 350 to 450°C.

[0053] In addition, the heating time (heating time: the time from when the heating temperature is reached) can also be adjusted appropriately depending on the type and amount of plastic to be decomposed, the type and amount of zeolite catalyst and solvent used, and the reaction temperature described above, but it is preferable for the heating time to be approximately 10 minutes or more, more preferably 20 to 90 minutes, and particularly preferably 30 to 60 minutes.

[0054] In the present invention, the decomposition of plastics and the like is promoted by heating and reacting them, but depending on the selection of the types of plastics, solvents, and catalysts (or a combination thereof), the reaction may proceed before reaching the above temperature (heating temperature), and when the temperature is reached, the reaction may have progressed to a certain extent or almost completely. Therefore, the heating temperature and heating time described above are merely guidelines when carried out in a batch (batch) system, for example, and the heating time may be 0 to 60 minutes after reaching a predetermined (desired) temperature that is considered to be the heating temperature, when the temperature rise (preheating) time up to that point is about the above heating time. In addition, in an industrial case where raw materials such as plastics and catalysts are continuously supplied and the reaction product is continuously taken out instead of in a batch (batch) system, the heating time may be the operation time of the device. In this case, the residence time inside the device (set to the heating temperature) may be in the range of 1 to 90 minutes (more preferably, 1 to 60 minutes). In other words, the heating temperature and heating time are the temperature and time required to decompose the plastic (and the solvent (light oil)) using a zeolite catalyst, and may be appropriately determined depending on the circumstances, etc., and the above range is merely one example.

[0055] The reaction is preferably carried out under nitrogen purging conditions, such as a pressure of 0.1 to 2.0 MPa, but is not limited to this range.

[0056] The mass ratio of the solvent and catalyst used to the plastic to be decomposed is preferably such that, when the plastic is taken as 1, the mass of the solvent is 2 to 10, and the mass of the catalyst is 0.05 to 0.4.

[0057] After the reaction is completed, it is preferable to cool the reaction mixture to room temperature. After cooling, it is preferable to separate the following decomposed components, if necessary.

[0058] In the decomposition method according to the present invention, it is believed that plastics are decomposed into roughly the following 14 components (1) to (14).

[0059] (Decomposed components) (1) Carbon Residue: Carbon residue (2) Residue + Catalyst: Solid residue (residue + catalyst) (3) Solvent: Solvent (4) C1~C2 Aliphatic: C1~C2 aliphatic (5) C3~C4 Aliphatic: C3~C4 aliphatic (6) C5~C9 Aliphatic: C5~C9 aliphatic (7) C6~C9 Monocyclic: C6~C9 monocyclic (8) C 10 ~C 16 Aliphatic: C 10 ~C 16 Aliphatic (9) C 17 ~C 19 Aliphatic: C 17 ~C 19 Aliphatic (10) C9< Monocyclic : C9< monocyclic (11) Dicyclic: Bicyclic (12) Tricyclic~: Tricyclic~ (13) C 29 ~C 44 : C 29 ~C 44 (14) C 44 <: C 44 <

[0060] In addition, as means for separating these respective components (gas products, liquid products, solid products (referring to residues and catalysts)), the means described in the following [Examples] can be used, but are not limited thereto. Other than this, gas products, liquid products, solid products, etc. can be separated using conventionally known separation means.

[0061] As petrochemical raw materials, generally, C3~C9 components, namely (5) C3~C4 aliphatic, (6) C5~C9 aliphatic, and (7) C6~C9 monocyclic (among petrochemical raw materials, in particular, (6) C5~C9 aliphatic is preferred) are considered to be usable.

[0062] (III) Effect of the invention: According to the plastic decomposition method of the present invention described above, plastics including waste plastics are mixed with a zeolite catalyst and diesel fuel as a solvent, and are heated to react and decompose the plastics. Thus, the zeolite catalyst promotes the decomposition of plastics, and the use of diesel fuel as a solvent increases the fluidity of the plastics to be decomposed, eliminating the problem of high viscosity when the plastics are heated and melted. As a result, plastics including waste plastics can be heated quickly and uniformly, decomposed at a high decomposition rate, and have high decomposition ability, and C3 to C9 components that can be used as petrochemical raw materials can be obtained in high yields.

[0063] According to the decomposition method of the present invention, it is expected that the decomposition rate (conversion rate) of plastics including waste plastics will be 80% or more (more preferably 90% or more), and the yield of the components (5) to (7), which are C3 to C9 components that can be used as petrochemical raw materials, will be 50% or more.

[0064] The plastic decomposition method according to the present invention is optimal as a method for decomposing waste plastics, which are decomposed as waste plastics. That is, by decomposing the waste plastics as the decomposition target with a zeolite catalyst using a light oil such as LGO, which is a hydrocarbon solvent obtained from petroleum refining, as the solvent used, the waste plastics can be decomposed at a high decomposition rate, and C3 to C9 components that can be used as petrochemical raw materials can be obtained in high yields, making it possible to easily carry out chemical recycling.

[0065] In addition, the light oil, which is the solvent used, can be obtained as a hydrocarbon solvent obtained by petroleum refining, and it is assumed that the plastic decomposition oil obtained by the decomposition method of the present invention will also be a hydrocarbon solvent with a similar composition to light oil solvents such as LGO and LCO. Therefore, it is possible that the solvent can also be provided from recycled products, and it is also possible to build a chemical recycling system using these.

[0066] (IV) Modifications of the embodiment: The above-described aspects show one aspect of the present invention, and the present invention is not limited to the above-described embodiments, and it goes without saying that modifications and improvements that have the configuration of the present invention and can achieve the object and effect are included in the contents of the present invention. Furthermore, the specific structure and shape, etc., when implementing the present invention may be other structures and shapes, etc., as long as the object and effect of the present invention can be achieved. The present invention is not limited to the above-described embodiments, and modifications and improvements that can achieve the object of the present invention are included in the present invention.

[0067] For example, in the above explanation, alkali treatment of a zeolite catalyst, debasing treatment of a solvent, hydrogenation treatment, etc. are given as examples of predetermined methods, but there is no problem if a method other than the predetermined methods given as examples is used as long as it corresponds to alkali treatment of a zeolite catalyst, debasing treatment of a solvent, hydrogenation treatment, etc. and does not impede the objects and effects of the present invention.

[0068] Similarly, the fluoride method, which is a means for synthesizing a zeolite catalyst, has been described using a specific method as an example, but there is no problem if a method other than the specific method given as an example is used to implement the present invention as long as it does not impede the objects and effects of the present invention. In addition, the specific structure and shape when implementing the present invention may be other structures and shapes within the scope of the invention in which the object of the present invention can be achieved. EXAMPLES

[0069] The present invention will now be described in more detail with reference to the following examples and reference examples, but the present invention is not limited to these.

[0070] Note that [Test Example 1] described below is a reference example that mainly shows the difference in plastic decomposition ability and the yield of each component between paraffinic solvents and aromatic solvents, and [Test Example 3] is also a reference example that mainly uses paraffinic solvents and shows the difference in plastic decomposition ability and the yield of each component depending on whether or not the zeolite catalyst is subjected to alkaline treatment.

[0071] [Test Example 1] Decomposition of Plastics (1): Plastic (polypropylene: PP) was decomposed using the following method (the following operations are referred to as "basic operations").

[0072] A batch reactor (reactor) having a capacity of 100 ml containing 20.0 g of solvent (see (Solvent 1) and (Solvent 2) below for the solvents used in Test Example 1) was charged with 5.0 g of polypropylene (M w =370000: JPEC) and 1.0 g of a granular (particulate) Beta zeolite catalyst (synthetic zeolite (high silica zeolite HSZ (registered trademark) HSZ-900 931HOA Si / Al=15.1, manufactured by Tosoh Corporation, average particle size: 0.933 μm) (catalyst 1) as a zeolite catalyst were mixed to prepare a mixed solution. The Beta zeolite catalyst used is a 12-membered ring zeolite catalyst having 12-membered ring pores in the three-dimensional direction.

[0073] The resulting mixed solution was purged with nitrogen at 0.1 MPa to create a nitrogen atmosphere. In this state, the temperature was increased at a rate of about 10°C / min until it reached 400°C, and the reaction was allowed to proceed by maintaining the temperature at 400°C for 60 minutes. During the reaction, the mixture was stirred at 400 rpm.

[0074] (Solvent used in Test Example 1) Solvent 1: Paraffinic solvent (n-hexadecane) (Table 2, etc., nC 16 There are also some places that say.) Solvent 2: Aromatic solvent (1-methylnaphthalene) (Table 2, etc., sometimes written as 1-MN)

[0075] The BET specific surface area (S BET ), outer surface area (S External ), micropore volume (V micro ), mesopore volume (V meso ) are shown in Table 1.

[0076] (BET specific surface area, etc. (catalyst 1)) [Table 1]

[0077] (Separation of each component) After the reaction was completed, the mixture was cooled to room temperature and separated into gaseous components, liquid components, and solid products (referring to residue and catalyst; the same applies below) using the method described below. Each component was analyzed to evaluate the plastic decomposition rate (conversion rate) and the products.

[0078] After the reaction was completed, the mixture was cooled to room temperature. First, the gaseous products were recovered by water displacement, and the concentration of each component was measured using a gas chromatography-flame ionization detector (GC-FID).

[0079] In addition, the mixture after gas recovery was cooled to -10 to 10°C together with the reactor to prevent vaporization of C5 and C6, and used as an internal standard sample. This internal standard sample was filtered using a Minisart to separate the liquid product from the other solid products.

[0080] The liquid product was collected and the solvent decomposition rate was calculated by GC-FID. In addition, the product distribution was measured by GC-MS and distillation GC. On the other hand, the solid product was collected after suction filtration, solvent replacement (n-pentane (n-C5) was used), dried overnight, and the mass (M SP The dried solid product was then dissolved in o-dichlorobenzene and filtered, and the collected insoluble matter was dried. The dried insoluble matter was then kept in air at 600°C for 30 minutes, and the mass of the carbon residue deposited on the catalyst (M CR ) (g: the same applies to the other masses.) was calculated.

[0081] (Calculation of decomposition rate and yield) Based on the mass measurement results of each separated component (corresponding to (1) to (14) of the "decomposed components" described above), the carbon residue (M CR ), residue (M R In this test, the plastic and the solvent were decomposed by the catalyst (zeolite catalyst), so it is impossible to identify the raw materials of the obtained products (gas product and liquid product). Carbon residue (M CR ) = Initial mass of waste material - Mass after heat treatment in air at 600℃ for 30 minutes Residue (M R ) = mass of solid product (M SP )-Carbon residue (M CR )-Catalyst mass (M C )

[0082] To investigate the decomposition products derived from plastics in a solvent, the yield of each component was calculated when the solvent and plastic were used and when only the solvent was reacted, and the yield of the product derived from the plastic was calculated from the difference in the yield of each component. The decomposition rate and yield were calculated using the following method.

[0083] The decomposition rate (conversion rate) is calculated based on the mass (M P ) and the mass of the solid product recovered at room temperature after the reaction (M SP ) to the mass of the catalyst used (M C ) and the mass of the carbon residue deposited on the catalyst (M CR ) and calculated using the following formula (X). Even if plastic decomposed, if it was recovered as a solid product at the time of recovery, it was considered not to have been decomposed (hereinafter, mass% may simply be referred to as "%"). The decomposition rate of the solvent was calculated in the same manner by quantifying the liquid product by gas chromatography (GC) and confirming the difference in mass from the increase or decrease. Decomposition rate [%]=(100-(M SP -M C -M CR ) / M P )×100 …… (X)

[0084] The yield [%] of each component is calculated by subtracting the ratio (mass%) of each component before the reaction from the ratio (mass%) of each component after the reaction to the whole to obtain the increase or decrease Δw (mass%), dividing the increase or decrease Δw (mass%) by the total Δw (for solvent 1, this corresponds to 23.940 (mass%) in Table 3), and expressing it as a percentage (multiplying by 100) (see formula (Y) below). Yield [%] = (sum of Δw / Δw) × 100 …… (Y)

[0085] In calculating Δw, the yield was calculated using 21.0g, which is the sum of the solvent (20.0g) and catalyst (1.0g), as the denominator. In the absence of polypropylene (solvent only), the total is (21.0g / 21.0g) x 100(%) = 100%. On the other hand, in the presence of polypropylene, the total is (21.0g + 5.0g (mass of polypropylene) / 21.0g) x 100(%) = (24.0g / 21.0g) x 100(%) ≒ 124%.

[0086] (Results: Test Example 1 (Decomposition rate) [Table 2]

[0087] (Results: Test Example 1 (Yield)) [Table 3]

[0088] Solvent 1 (n-hexadecane (nC 16) (paraffin-based solvent) was used, as shown in Table 2, the decomposition rate of polypropylene (sometimes referred to as "PP" in Table 2, etc.; the same applies to other places) was 97.9%, and the decomposition rate of the solvent was 96.9%, and as shown in Table 3, the yield of C5 to C9 aliphatic components, which are petrochemical raw materials, was 59.4%, and the total of C3 to C9 components was 57.7%. (Note that the yield values ​​in this column and other explanations are sometimes given with significant figures to one decimal place for the values ​​given in the table (rounded off to one decimal place).)

[0089] Furthermore, the decomposition rate of n-hexadecane when polypropylene was not used was 97.7%, and no significant difference was observed in the decomposition of the solvent with or without polypropylene. The fact that there was no significant difference in the decomposition rate of the solvent with or without polypropylene indicates that polypropylene and the solvent are decomposed independently in the presence of the catalyst, and that the interaction between polypropylene and the solvent is small.

[0090] On the other hand, when solvent 2 (1-methylnaphthalene (aromatic solvent)) was used, as shown in Table 2, the decomposition rate of polypropylene was 68.2%, and the decomposition rate of the solvent was only 72.6%. As shown in Table 3, the yield of C5 to C9 aliphatic components, which are petrochemical raw materials, was 24.7%, and the total yield of C3 to C9 components was 44.8%.

[0091] Furthermore, the decomposition rate of n-hexadecane when polypropylene was not used was 48.2%, as shown in Table 2, and a significant difference was observed in the decomposition of the solvent depending on whether polypropylene was used or not.

[0092] In addition, in Test Example 1, Solvent 1 (n-hexadecane) and Solvent 2 (1-methylnaphthalene) were mixed to make the blending ratio of Solvent 1 / Solvent 2 = 7 / 3 and 3 / 7, and the results were confirmed in the same manner. The results of Test Example 1 (solvent 1 only, solvent 2 only) are shown in Table 4.

[0093] (Results: Test Example 1 (Relationship between the blending ratio of solvent 1 and solvent 2)) [Table 4]

[0094] From the results in Table 4, it was confirmed that the decomposition rate of polypropylene increases as the blending ratio of n-hexadecane (paraffin-based solvent) in the solvent increases.

[0095] From the above, it was confirmed that the use of the paraffinic solvent n-hexadecane improves the catalytic decomposition rate of polypropylene (to 90% or more) compared to the use of the aromatic solvent 1-methylnaphthalene, and also increases the yield of C3 to C9 components (especially C5 to C9 components), which are petrochemical raw materials, exceeding 50%.

[0096] [Test Example 2] Decomposition of Plastics (2): When using LGO (Light Gas Oil), a petroleum fraction supplied from petroleum refineries, as a solvent, it is believed that the decomposition rate of plastics can be increased by removing the basic substances in the solvent through debasing treatment or by hydrogenating the solvent, and this was confirmed in this test.

[0097] In Test Example 2, plastic (polypropylene) was decomposed using the same procedure as Test Example 1, except that the following solvents 3, 4, and 5 were used as the hydrocarbon solvents. Solvents 4 and 5 are a common solvent, light oil LGO (Light Gas Oil) (evaluated as solvent 3 as a reference example), whereas solvent 4 has been subjected to a debasing treatment and solvent 5 has been subjected to a hydrogenation treatment (the method of decomposing plastic (polypropylene) using solvent 3 is a reference example, and the methods of decomposing plastic (polypropylene) using solvents 4 and 5 are examples).

[0098] (Hydrocarbon Solvent Used in Test Example 2) Solvent 3: LGO (Light Gas Oil) Solvent 4: Solvent 3 debasified Solvent 5: Solvent 3 hydrogenated

[0099] (Debasing treatment) Amorphous silica alumina (N632-L: manufactured by JGC Catalysts and Chemicals Co., Ltd.), which is a solid acid, was milled and classified to have a particle size of 250 to 500 μm. This amorphous silica alumina was added to the target solvent (solvent 3, LGO, in this test) at a ratio of 5 mass %. After addition, the rotation speed was set to 300 rpm and stirring was performed for 48 hours to allow the basic substance to be adsorbed by the solid acid. After adsorption, the mixture was filtered to obtain debased LGO (RBC (Removal of Basic Compounds)-LGO).

[0100] (Hydrotreatment) The LGO in solvent 3 was subjected to hydrotreatment (hydrodesulfurization) according to a conventionally known hydrotreatment method under the following conditions to obtain hydrotreated LGO (HDS (hydrodesulfurization)-LGO).

[0101] (Hydrotreatment conditions) Catalyst: Cobalt-molybdenum (Co-Mo) desulfurization catalyst Hydrogen pressure: 4.9MPa ·Temperature: 350℃ ·Liquid hourly space velocity (LHSV): 0.93 / hour (LHSV:Liquid Hourly Space Velocity) H2 / Oil ratio: 260NL / L

[0102] The properties of the LGO solvent used are shown in Table 5, the compositions of LGO, RBC-LGO, and HDS-LGO are shown in Table 6, and the results are shown in Table 7 (decomposition rate) and Table 8 (yield).

[0103] (Properties of LGO) [Table 5]

[0104] (Composition of LGO, RBC-LGO and HDS-LGO) [Table 6]

[0105] (Results: Test Example 2 (Decomposition rate)) [Table 7]

[0106] (Results: Test Example 2 (Yield)) [Table 8]

[0107] For solvent 3 (untreated LGO), the decomposition rate of polypropylene was 50.9%, which was significantly lower than when solvent 1 (n-hexadecane) was used, as shown in Table 7. In addition, as shown in Table 8, the yield of C5-C9 aliphatic compounds, which are petrochemical raw materials, was -14.2%, and the total yield of C3-C9 components was -36.4%.

[0108] On the other hand, when solvent 4 (RGO-LGO), which was obtained by debasing solvent 3, was used as the solvent, the decomposition rate of polypropylene was 97.0%, as shown in Table 7, which was significantly improved compared to solvent 3. In addition, as shown in Table 8, the yield of C5-C9 aliphatic compounds, which are petrochemical raw materials, was 73.8%, and the total yield of C3-C9 components was 73.5%, which was also significantly increased compared to solvent 3.

[0109] When solvent 5 (HDS-LGO), which was obtained by subjecting solvent 3 to hydrogenation (hydrodesulfurization), was used as the solvent, the decomposition rate of polypropylene was 98.9%, as shown in Table 7, which was significantly improved compared to solvent 3. Furthermore, as shown in Table 8, the yield of C5 to C9 aliphatic compounds, which are petrochemical raw materials, was 52.6%, and the total yield of C3 to C9 components was 62.4%, which was also significantly increased compared to solvent 3.

[0110] From the above, it was confirmed that the plastic decomposition method using a debased solvent (solvent 4: RBC-LGO) and the plastic decomposition method using a hydrogenated solvent (solvent 5: HDS-LGO) improved the catalytic decomposition ability of polypropylene (to over 90%) compared to the use of a solvent that had not been subjected to these treatments (solvent 3: LGO), and also that the yield of C3 to C9 components (especially C5 to C9 components), which are petrochemical raw materials, was high, exceeding 50%.

[0111] [Test Example 3] Decomposition of Plastics (3): A plastic (polypropylene) was decomposed using the same procedure as in Test Example 1, except that 0.5 g of the following catalysts 2 to 4 were used instead of 2.0 g of catalyst 1, solvent 1 was used as the hydrocarbon solvent, and the heating temperature was changed from 400°C to 380°C.

[0112] Catalyst 3 and solvent 4 were obtained by subjecting catalyst 2 produced by the method described below (fluoride method) to an alkali treatment by the method described below.

[0113] (Catalyst used in Test Example 3) Catalyst 2: Beta zeolite catalyst produced by the following method (fluoride method) (Outer surface area (S External ):101m 2 / g), Si / Al: 24.6) Catalyst 3: Zeolite catalyst obtained by subjecting Catalyst 2 to the alkali treatment (1) described below. (Outer surface area (S External ):139m 2 / g), Si / Al: 21.8) Catalyst 4: Zeolite catalyst obtained by subjecting Catalyst 2 to the alkali treatment (2) described below. (Outer surface area (S External ):212m 2 / g), Si / Al:20.0)

[0114] (Production of Beta Zeolite Catalyst by Fluoride Method) 8.0 g of fumed silica (SiO2), 13.86605 g of tetraethylammonium hydroxide (TEAOH), and 2.5169 g of ammonium fluoride (NH4F) were placed in a PTFE beaker (beaker A). 13.86605 g of tetraethylammonium hydroxide (TEAOH) and 0.2706 g of aluminum hydroxide (Al(OH)3) were placed in another PTFE beaker (beaker B), and the mixture was stirred at room temperature for 0.5 hours (30 minutes).

[0115] The stirred solution in beaker B was poured into beaker 1 and further stirred (the composition of the synthesis gel after stirring was as follows), and then aged at 40°C for 3 hours. After aging, hydrothermal synthesis was carried out at 150°C for 96 hours, filtered, and then dried overnight at 60°C. The ammonium ion (NH4 + )-exchanged Beta zeolite catalyst was calcined at 550°C for 10 hours to obtain hydrogen ions (protons H + ) exchanged Beta zeolite catalyst (Catalyst 2) was obtained.

[0116] (Synthetic gel composition) SiO2 / Al2O3 / NH4F / TEAOH / H2O=1.00 / 0.0125 / 0.50 / 0.50 / 7.6(Si / Al=40)

[0117] (Alkaline treatment (1)) A PTFE beaker was charged with 400 ml of 0.03 M aqueous sodium hydroxide solution at 60°C and heated to 60°C. 4.0 g of catalyst 2 (Beta zeolite catalyst) synthesized by the fluoride method was then immersed in the solution and stirred at 400 rpm for 10 minutes to prepare a mixture.

[0118] This mixture was filtered under reduced pressure while washing with distilled water until the washings became neutral, and the collected solid was then dried overnight in an oven at 70°C. The entire amount of this zeolite powder was then placed in a 1.0 M aqueous sodium nitrate solution (120 ml) at 80°C, and the mixture was stirred at this temperature for 1 hour to carry out ion exchange, followed by filtering under reduced pressure. This procedure was repeated twice, and then the mixture was dried overnight at 70°C. The dried sample was heated to 550°C in a muffle furnace at a rate of 5°C / min, and then held at 550°C for 10 hours to obtain a beta zeolite catalyst (catalyst 3) that was alkali-treated on catalyst 2.

[0119] (Alkaline treatment (2)) A beta zeolite catalyst (catalyst 4) was obtained by subjecting catalyst 2 to an alkali treatment in the same manner as in the alkali treatment (1), except that 400 ml of 0.1 M aqueous sodium hydroxide solution was used instead of 400 ml of 0.03 M aqueous sodium hydroxide solution in the alkali treatment (1).

[0120] The BET specific surface area (S BET ), outer surface area (S External ), micropore volume (V micro ), mesopore volume (V meso ) are shown in Table 9, and the results are shown in Table 10 (decomposition rate) and Table 11 (yield). The average particle diameters of Catalysts 2 to 4 were 3 to 5 μm.

[0121] (BET specific surface area, etc. (catalyst 2 to catalyst 4)) [Table 9]

[0122] (Results: Test Example 3 (Decomposition rate) [Table 10]

[0123] (Results: Test Example 3 (Yield)) [Table 11]

[0124] As shown in Table 10, when catalyst 2 was used, the decomposition rates of polypropylene and solvent were 9.0% and 62.1%, respectively. In addition, as shown in Table 11, the yield of C5-C9 aliphatic compounds, which are petrochemical raw materials, was 31.7%, and the total yield of C3-C9 components was 34.8%.

[0125] It is believed that by using a zeolite catalyst with a similar acid density (Si / Al ratio of about 20), it will be possible to confirm the effect on polypropylene decomposition of the increase in external surface area due to alkali treatment, rather than the amount of acid. When catalyst 3, which was obtained by alkali-treating catalyst 2, was used, the decomposition rates of polypropylene and solvent were 13.6% and 80.5%, respectively. In addition, the yield of C5-C9 aliphatic compounds, which are petrochemical raw materials, was 35.3%, and the total yield of C3-C9 components was 44.6%.

[0126] When catalyst 4, which was prepared by treating catalyst 2 with an alkali, was used, the decomposition rates of polypropylene and solvent were 54.0% and 80.2%, respectively. The yield of C5-C9 aliphatic compounds, which are petrochemical raw materials, was 49.1%, and the total yield of C3-C9 components was 59.5%.

[0127] From the above, it was revealed that alkali treatment of the Beta zeolite catalyst produced by the fluoride method can improve the decomposition of plastics (polypropylene) and also improve the yield of C3 to C9 components, which are petrochemical raw materials.

[0128] Figure 1 shows the relationship between the external surface area and the decomposition rate. The external surface area of ​​the Beta zeolite catalyst increases with alkali treatment, and from Figure 1, it appears that the increase in external surface area promotes the decomposition of polypropylene more effectively than the solvent. The decomposition rates of polypropylene and solvent 1 (n-hexadecane), a paraffin-based solvent, increase as the external surface area of ​​the Beta zeolite catalyst increases, and it was confirmed that the decomposition rate of polypropylene in particular increases in response to the increase in the external surface area of ​​the Beta zeolite catalyst. [Industrial Applicability]

[0129] The present invention can be advantageously used as a means for providing a method for easily decomposing waste plastics including polypropylene, polyethylene, polystyrene, etc., and obtaining C3 to C9 components that can be used as petrochemical raw materials in high yields, and has high industrial applicability.

Claims

1. A method for decomposing plastics, comprising using debased and / or hydrotreated diesel as a solvent, mixing plastics (including waste plastics) with a zeolite catalyst, and heating to cause a reaction.

2. 2. The method for decomposing plastics according to claim 1, wherein the zeolite catalyst has a 10-membered ring or a 12-membered ring.

3. 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the zeolite catalyst is a 12-membered ring Beta zeolite catalyst.

4. 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the light oil is LGO (Light Gas Oil).

5. 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the zeolite catalyst is one which has been treated with an alkali.

6. The method for decomposing plastics according to claim 1 or 2, characterized in that the heating temperature is 350 to 450°C.

7. 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the plastics are waste plastics.

8. 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the decomposition rate of the plastics is 80% or more.

9. C 3 ~C 9 3. The method for decomposing plastics according to claim 1 or 2, characterized in that the yield of the components is 50% or more.

Citation Information

Patent Citations

  • Displacement-amount conversion apparatus

    JP1986030358A

  • Method for treating composition containing thermoplastic resin

    JP2018520247A

  • Method for treating composition containing thermoplastic resin

    JP2018524448A

  • Method for producing pyrolysis oil from waste plastics, and waste plastic oil production plant

    JP7258270B1